The evolution of the geothermal potential of a subsurface urban heat island. (1st August 2022) - Hemmerle, Hannes; Ferguson, Grant; Blum, Philipp; Bayer, Peter
Abstract: Meeting the rising energy demands of cities is a global challenge. Exploitation of the additional heat in the subsurface associated with the subsurface urban heat island (SUHI) has been proposed to address the heating demands. For the sustainable use of this heat it is crucial to understand how SUHIs evolve. To date, there have been no comprehensive studies showing how temperature anomalies beneath cities change over time scales of decades. Here, we reveal the long-term increase of temperatures in the groundwater beneath Cologne, Germany from 1973 to 2020. The rise in groundwater temperature trails atmospheric temperature rise in the rural areas and exceeds the rise in atmospheric temperature in the urban center. However, the amount of heat that is currently stored each year in the thin shallow aquifer reaches only 1% of the annual heating demand. The majority of the anthropogenic heat passes by the vertical extent of the aquifer or is discharged by the adjacent river. Overall the geothermal resource of the urban ground remains largely underused and heat extraction as well as combined heating and cooling could substantially raise the geothermal potential to supply the city's demand.